A People's History of Classics : Class and Greco-Roman Antiquity in Britain and Ireland 1689 To 1939 - Hall, Edith (Taylor & Francis Group, 2020)
Cover -- Half-Title -- Title -- Copyright -- Dedication -- Contents -- List of maps -- List of figures -- Maps of locations discussed in the text -- Preface -- Part I Canons, media and genres -- 1 Motives and methods -- 2 The invention of Classics and the emergence of class -- 3 Working-class readers -- 4 18th-century working-class poets -- 5 Classics and class in life-writing -- 6 Working-class Classics via the visual environment -- 7 Staging class struggle classically -- Part II Communities -- 8 Dissenting Classics -- 9 Adult education -- 10 Classics and class in Ireland -- 11 Scottish working Classics -- 12 Caractacus and Lloyd George's recruiting drive in Wales -- Part III Underdogs, underclasses, underworlds -- 13 Seditious classicists -- 14 Underdog professors -- 15 Ragged-trousered philologists -- 16 Hinterland Greek -- 17 Classical underworlds -- 18 Class and the classical body -- Part IV Working identities -- 19 Gods and heroes of the proletariat -- 20 Shoemaker Classics -- 21 Pottery workers -- 22 Classics amongst the miners -- 23 Socialist and communist scholars -- 24 Soldiers: Dai and Diomedes on the Somme -- 25 Theatre practitioners -- Afterword -- References -- Index.